Ketedasan Terjemahan Ayat-Ayat Imperatif Bernuansa Budaya - Mohamad Zaka Al Farisi (el Harakah: Jurnal Budaya Islam, 2017)
Each language has its own uniqueness because of the existence of cultural concepts that exist in it. To bring clarity to the translation of the nuanced cultural speech, including those contained in the imperative verses, often becomes an obstacle in translation. The study, which used a qualitative-evaluative approach with the design of embedded case study research, aims to reveal the clarity of the translation of imperative verses that have cultural nuance meanings. Samples were selected purposively regarding imperative verses that have specific pragmatic meanings. The clarity of the translation of the imperative verses relies on the techniques and procedures of translation applied in dealing with micro-translation units. Couplet procedure that combines literal and amplification techniques may fulfill clarity aspect in translation. Setiap bahasa mempunyai keunikan tersendiri berkat keberadaan konsep-konsep budaya yang ada di dalamnya. Dalam penerjemahan, menghadirkan ketedasan terjemahan tuturan yang bernuansa budaya, termasuk dalam ayat-ayat imperatif, seringkali menjadi kendala tersendiri. Penelitian ini, yang menggunakan pendekatan kualitatif-evaluatif dengan desain studi kasus terpancang, bertujuan untuk mengungkap ketedasan terjemahan ayat-ayat imperatif yang bernuansa budaya. Sampel penelitian dipilih secara purposif berupa ayat-ayat imperatif yang memiliki makna pragmatik tertentu. Ketedasan terjemahan ayat-ayat imperatif tidak terlepas dari teknik dan prosedur penerjemahan yang diterapkan dalam menangani unit-unit mikro terjemahan. Prosedur kuplet yang memadukan teknik literal dan teknik amplifikasi dapat menghadirkan ketedasan terjemahan yang berterima.